براہوئی گیدی سوت: Brahui Folk South - Sadiq, Abdul Haleem; Baloch, Manzoor; Nazir, Iqbal; Rasool, Zahida Guhlam (Hanken, 2013)
Brahui language is rich in folk literature in both forms, prose and poetry. In poetry the Gedi-sot (folk song) are based on various poetic forms like laili mor (love songs), bar nazana, laiko, hallo (marriage songs), loli (lullaby) and moda (elegy), etc. This paper discusses the various forms of Brahui folk songs including, barnazana, laili mor, mah lanj, lade laday, loli, zahiri, halo and moda. The Brahui Gedi-sot (folk songs) depicts women with various symbolic names, like Zeba (beautiful), Zebal (pretty), Zebjan (beautiful), Puljan (like flower), Guljan, (like flower), Mahlanj (beautiful than moon light), Bijli (electricity), Laadi (delicately nurtured or brought up), Jaanal (part of body), etc. The Brahui Gedi-sot is till today popular and common in Brahui speaking areas of the world.